Pelayanan Pastoral Secara Holistik Bagi Orang Sakit Berdasarkan Perspektif Alkitabiah - Permana Hutabarat, Risky; Wahyuni, Sri (Kaluteros Jurnal Teologi Dan Pendidikan Agama Kristen, 2025)
Holistic pastoral care for the sick is a comprehensive approach that addresses spiritual, emotional, and physical needs. This study explores the concept of holistic pastoral care based on a biblical perspective and its implications for improving the spiritual quality of life of the sick. The findings show that holistic pastoral care can enhance the spiritual quality of life of the sick by providing emotional and spiritual support, facilitating spiritual experiences, increasing awareness of God's presence, and promoting hope and healing. This study contributes to the development of theory and practice of pastoral care in the context of healthcare